The melanocortin receptor type 3 agonist d‐Trp(8)‐γMSH decreases inflammation and muscle wasting in arthritic rats. Issue 1 (11th May 2015) - Gómez‐SanMiguel, Ana Belen; Martín, Ana Isabel; Nieto‐Bona, María Paz; Fernández‐Galaz, Carmen; Villanúa, María Ángeles; López‐Calderón, Asunción
Abstract: Background: Chronic inflammatory diseases induce cachexia that increases mortality and morbidity of the illness. Adjuvant‐induced arthritis is an experimental model of rheumatoid arthritis that is associated with body weight loss and muscle wasting. Alpha‐melanocyte stimulating hormone has an anti‐inflammatory effect in arthritic rats and decreases muscle wasting. The aim of this work was to elucidate whether the anti‐cachectic action of alpha‐melanocyte stimulating hormone is mediated by the melanocortin receptor type 3 pathway. Methods: Arthritis was induced in male Wistar rats by intradermal injection of Freund's adjuvant, and 6 days afterwards, arthritic rats were injected with the selective melanocortin receptor type 3 agonistd ‐Trp(8)‐gammaMSH (d ‐Trp(8)‐γMSH) 500 µg/kg subcutaneously. or saline twice a day, for 10 days. Results: d ‐Trp(8)‐γMSH decreased the external signs of inflammation and body weight loss, but it was not able to modify the anorexigenic effect of arthritis or the increase in hypothalamic cyclooxygenase‐2 (COX‐2) expression. In contrast, d ‐Trp(8)‐γMSH prevented arthritis‐induced increase in hypothalamic IL‐1β and serum corticosterone levels and the decrease in serum IGF‐I levels.d ‐Trp(8)‐γMSH treatment also prevented arthritis‐induced NF‐ k B(p65) phosphorylation and tumour necrosis factor‐α mRNA increase in the gastrocnemius.d ‐Trp(8)‐γMSH administration to arthritic rats increased gastrocnemius mass, its cross‐sectional area, and mean fast fibre area. Those effects ofd ‐Trp(8)‐γMSH were associated with a decreased expression of atrogin‐1 and muscle ring‐finger protein‐1 in the gastrocnemius. In rats treated with saline, arthritis increased the expression of autophagy marker genes LC3b, Bnip‐3, and Gabarap1 as well as the conversion of LC3b I to LC3b II by lipidation in the gastrocnemius.d ‐Trp(8)‐γMSH decreased gastrocnemius LC3b, Bnip‐3, and Gabarap1 mRNA expression and prevented the increase in LC3b II in arthritic rats. Conclusion: These data suggest thatd ‐Trp(8)‐γMSH administration prevents the effect of arthritis on corticosterone and insulin‐like growth factor‐I serum levels and decreases muscle wasting, by down‐regulating atrogenes and autophagy through modifying the NF‐ k B(p65)/tumour necrosis factor‐α signalling transduction pathway.